Benzophenone Synthase and Chalcone Synthase Accumulate in the Mesophyll of Hypericum perforatum Leaves at Different Developmental Stages - Belkheir, Asma K.; Gaid, Mariam; Liu, Benye; Hänsch, Robert; Beerhues, Ludger (Frontiers in Plant Science, 2016)
The active medicinal constituents in Hypericum perforatum, used to treat depression and skin irritation, include flavonoids and xanthones. The carbon skeletons of these compounds are formed by chalcone synthase (CHS) and benzophenone synthase (BPS), respectively. Polyclonal antisera were raised against the polyketide synthases from Hypericum androsaemum and their IgG fractions were isolated. Immunoblotting and immunotitration were used to test the IgGs for crossreactivity and monospecificity in H. perforatum leaf protein extract. Immunofluorescence localization revealed that both CHS and BPS are located in the mesophyll. The maximum fluorescence levels were observed in approx. 0.5 and 1 cm long leaves, respectively. The fluorescence intensity observed for CHS significantly exceeded that for BPS. Using histochemical staining, flavonoids were detected in the mesophyll, indicating that the sites of biosynthesis and accumulation coincide. Our results help understand the biosynthesis and underlying regulation of active H. perforatum constituents.